2018
DOI: 10.1371/journal.pone.0207841
|View full text |Cite
|
Sign up to set email alerts
|

Changes of diaphragmatic excursion and lung compliance during major laparoscopic pelvic surgery: A prospective observational study

Abstract: Major laparoscopic pelvic surgery requires steep Trendelenburg position with pneumoperitoneum for a long time. We investigated the effect of Trendelenburg position with pneumoperitoneum on diaphragmatic excursion and lung compliance during major laparoscopic pelvic surgery using M-mode sonography. Twenty patients undergoing elective pelviscopic radical hysterectomy were included in this study. Diaphragmatic excursion was measured at the following time points; after sedation, after intubation, 90 minutes after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Moreover, impaired diaphragmatic excursion at the end of surgery occurred more frequently in patients who underwent laparoscopic than in those who underwent open radical hysterectomy. Our previous study showed that laparoscopic radical hysterectomy reduced diaphragmatic excursion and lung compliance not only during the operation but also at the end of the surgery after neuromuscular reversal 3 . In addition, the present study found that laparoscopic radical hysterectomy worsened diaphragmatic excursion and lung compliance more than open radical hysterectomy did.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, impaired diaphragmatic excursion at the end of surgery occurred more frequently in patients who underwent laparoscopic than in those who underwent open radical hysterectomy. Our previous study showed that laparoscopic radical hysterectomy reduced diaphragmatic excursion and lung compliance not only during the operation but also at the end of the surgery after neuromuscular reversal 3 . In addition, the present study found that laparoscopic radical hysterectomy worsened diaphragmatic excursion and lung compliance more than open radical hysterectomy did.…”
Section: Discussionmentioning
confidence: 97%
“…This study enrolled 20 adult patients (American Society of Anesthesiologists physical status I–II) who prospectively underwent elective open radical hysterectomy. The control group consisted of 20 patients who had previously undergone laparoscopic radical hysterectomy 3 . Patients were excluded if they had chronic obstructive pulmonary disease, respiratory dysfunction, or a body mass index > 30 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the shorter condition increases the accuracy, the 33 cm-distant conditions were selected for the limits of laparoscopic procedures. Although a shift and deformation of 44.6 mm on average was assumed because of the combined effect of respiration and pneumoperitoneum [15][16][17][18] , errors of the simulation have been reported within 2 cm in recent studies 7,19 . However, the dynamic navigation technique based on an electromagnetic-tracked laparoscopic ultrasound-based navigation approach reported accurate and efficient targeting of liver tumours in a laparoscopic ablation as the median target-positioning error was 4.2 mm and median effort time was 39 sec 20 .…”
Section: Discussionmentioning
confidence: 99%
“…First, the patient is subjected to a peritoneal CO 2 absorption that will require an increase in CO 2 excretion by the lungs to preserve normocapnea 2,3 . Second, the increase in intra‐abdominal pressure (IAP) will cause an upward displacement of the diaphragm that will reduce end‐expiratory lung volume, which in turn will negatively influence ventilation and make adequate CO 2 removal more difficult 4 . In addition to this, maintaining stable CO 2 levels is particularly important in neonates and infants, were the CO 2 absorption seen during capnoperitoneum has been shown to proportionally increase with smaller age and size, 2 and fluctuations in PaCO 2 is a main factor in the regulation of cerebral blood flow and thus a key component in preventing of neurological injury 5‐7 …”
Section: Introductionmentioning
confidence: 99%